Simulation of Stomatal Conductance and Water Use Efficiency of Tomato Leaves Exposed to Different Irrigation Regimes and Air CO2 Concentrations by a Modified “Ball-Berry” Model - Wei, Zhenhua; Du, Taisheng; Li, Xiangnan; Fang, Liang; Liu, Fulai (Frontiers in Plant Science, 2018)
Stomatal conductance (gs) and water use efﬁciency (WUE) of tomato leaves exposed to different irrigation regimes and at ambient CO2 (a[CO2], 400 ppm) and elevated CO2 (e[CO2], 800 ppm) environments were simulated using the ‘Ball-Berry’ model (BB-model). Data obtained from a preliminary experiment (Exp. I) was used for model parameterization, where measurements of leaf gas exchange of potted tomatoes were done during progressive soil drying for five days. The measured photosynthetic rate (Pn) was used as an input for the model. Considering the effect of soil water deficits on gs, an equation modifying the slope (m) based on the mean soil water potential (Ψs) in the whole root zone was introduced. Compared to the original BB-model, the modiﬁed model showed greater predictability for both gs and WUE of tomato leaves at each [CO2] growth environment. The models were further validated with data obtained from an independent experiment (Exp. II) where plants were subjected to three irrigation regimes: full irrigation (FI), deﬁcit irrigation (DI) and alternative partial root-zone irrigation (PRI) for 40 days at both a[CO2] and e[CO2] environment. The simulation results indicated that gs was independently acclimated to e[CO2] from Pn. The modiﬁed BB-model performed better in estimating gs and WUE, especially for PRI strategy at both [CO2] environments. A greater WUE could be seen in plants grown under e[CO2] associated with PRI regime. Conclusively, the modiﬁed BB-model was capable of predicting gs and WUE of tomato leaves in various irrigation regimes at both a[CO2] and e[CO2] environments. This study could provide valuable information for better predicting plant WUE adapted to the future water-limited and CO2 enriched environment.